Dinuclear helicate and tetranuclear cage assembly using appropriately designed ditopic triazole-azine ligands. Issue 41 (29th May 2019) - Singh, Sandhya; Hogue, Ross W.; Feltham, Humphrey L. C.; Brooker, Sally
Abstract : Architecture, helicate or cage, is controlled by choice of meta vs . para phenylene linker in new, robust, ditopic triazole-pyrimidine ligands. Abstract : Four new, symmetrical, bis-bidentate ditopic Rdpt -type, Rat (R a zine-t riazole), ligands have been prepared, L n pym- meta / para ( n = 2 or 4), which contain bidentate n -pyrimidine/triazole binding pockets connected through an appropriate aromatic spacer, meta / para -phenyl, to enable assembly into dinuclear helicates or tetranuclear tetrahedral cages, respectively. The 3 : 2 self assembly reactions of each L n pym- meta / para ligand with iron(ii ) tetrafluoroborate gave the desired complexes, as shown by X-ray crystal structure determinations of the pair of helicates [FeII2(L n pym- meta )3 (BF4 )4 ]·6CH3 CN, with n = 2 (1 ·6CH3 CN) or 4 (2 ·6CH3 CN), and the pair of Td cages [FeII4(L n pym- para )6 (BF4 )8 ]· x solvent, with n = 2 (3 · x solvent) or 4 (4 · x solvent). Reversible Fe II/III processes at E m = 0.95 ± 0.05 V vs . 0.01 M AgNO3 /Ag in MeCN are a feature of 1–4, with little variation in the redox potential as a function of nuclearity, architecture or choice of n -pyrimidine isomer. In all four complexes the iron(ii ) centres are low spin, despite having employed the weakest field diazines, the 2- and 4-pyrimidines, in these ditopic Rat ligands. Nevertheless this is an exciting proof of principle that Rdpt -type ligands (previously used to generate about 50 spin crossover-active complexes) can be extended into ditopic forms that are suitable for supramolecular assembly of helicates and cages.